2021
DOI: 10.3390/ijerph18199991
|View full text |Cite
|
Sign up to set email alerts
|

Improving Treatment Adherence with Integrated Patient Management for TB Patients in Morocco

Abstract: In Morocco, there are challenges in the management of high-risk tuberculosis (TB) patients, including paper-based management and a shortage of healthcare workers related to TB. Additionally, TB management has not been accounted for in various patient types, which affects treatment adherence. This study aims to examine the delivery model of TB management and the outcomes of an integrated patient management system that uses a patient-centered and community-based approach, along with mobile health technology. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The introduction of telehealth reduced the rate of absenteeism for both video and in-person visits. In this small sample, it is a valuable tool for follow-up TBI and is preferred by patients living further away from the clinic 9 [ 19 ] This study aimed to examine TB management delivery models and outcomes from integrated patient management systems using patient-centered and community-based approaches, along with health technology Sample Population : A total of 3605 TB patients were enrolled in the program in five Moroccan prefectures (Rabat, Salé, Kénitra, Khemisset, Skhirat–Témara) from January 2018 to December 2019. Sample technique : A randomize sampling Retrospektif studi dengan tes chi-square Integrated patient management in the form of short message service (SMS) technology, and electronic pillboxes results in higher treatment success rates than existing programs in Morocco.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of telehealth reduced the rate of absenteeism for both video and in-person visits. In this small sample, it is a valuable tool for follow-up TBI and is preferred by patients living further away from the clinic 9 [ 19 ] This study aimed to examine TB management delivery models and outcomes from integrated patient management systems using patient-centered and community-based approaches, along with health technology Sample Population : A total of 3605 TB patients were enrolled in the program in five Moroccan prefectures (Rabat, Salé, Kénitra, Khemisset, Skhirat–Témara) from January 2018 to December 2019. Sample technique : A randomize sampling Retrospektif studi dengan tes chi-square Integrated patient management in the form of short message service (SMS) technology, and electronic pillboxes results in higher treatment success rates than existing programs in Morocco.…”
Section: Resultsmentioning
confidence: 99%
“…Tuberculosis, due to its infectious nature, increasing antimicrobial resistance and prevalence in low-and-middle-income (LMIC) countries, for example, India [28], Pakistan [29] Afghanistan [30], Morocco [13,31], Kenya [32,33], and Uganda [3,[34][35][36][37] has been widely studied. Characteristically, these previous studies gathered demographic and medical histories of a cohort and observed their adherence and outcomes.…”
Section: Previous Machine Learning Related Work In Tuberculosismentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 6, 2022. ; https://doi.org/10.1101/2022.12.01.22283003 doi: medRxiv preprint have not adequately used machine learning (ML) as a method to generate predictors of treatment non-adherence. Yet, ML models have been proven effective in accurately illustrating the target parameters for implementing stakeholders to ensure adherence to TB treatment (32,33). Therefore, a machine learning approach, incorporating the comprehensive patient and clinical features as captured in the health facility register for modeling, could prove beneficial.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%